Definition of residual operation resource of starter batteries by way of impedance research at different service terms - Makogon, Helen; Vasylenko, Denys; Potapov, Den; Piskun, Serghij; Bazilevskij, Igor; Ivanov, Vladimir; Klimov, Alexej; Prichina, Volodymir; Zobnin, Aleksej (Національний технічний університет "Харківський політехнічний інститут", 2019)
The subject matter of the article is the physicochemical processes occurring in a battery under different conditions and operating times. The goal of the study is to develop, a methodology for estimating the residual life-span of the batteries to make recommendations on the extension of their service life on the basis of an analysis of the conditions of use of the batteries. The tasks to be solved are: to analyze the influence of starter battery conditions on their performance and service life; to analyze the existing methods of determining the residual life of the batteries; to study the dependences of the deviation of the impedance fromthe standard value for the batteries at different moments of their normal life and to develop a method for predicting the residual life of the rechargeable batteries (RB). Generalscientific and special methods of scientific knowledge are used. The following results are obtained. On the basis of the readings of the ammeter and voltmeter when switching on the battariesin the circuit at different load values and according to the data obtained during the control-training cycle (CTC), the dependence of the impedance deviation from the base value at different regular battery life was investigated. According to the proposed method, it is easy to determine in which batteries the degradation has just begun and in which they have reached the level when they need tobe replaced without waiting for a fatal failure, by obtaining a minimum number of values of the electric parameters of the battery and comparing the data obtained at different times. Proper selection of chargers, skilled operation and timely monitoring of battary'sresidual life are the most important requirements for their operation. In full-time batteries, the internal resistance begins to increase over time due to natural wear and tear. Significant deviation from the norm in the smaller side indicates aclear malfunction sucha battery must be replaced regardless of its useful life. When the deviation from the baseline exceeds 25%, itis time to replace the battery. The conducted studies revealed nonlinear relationships between the battery life and its predicted residual life. Conclusions. Ensuring that the equipment is ready for use depends largely on the state of the RB. The greatest impact on the performance and life of the batteries is due to the temperature conditions, the degree of sparseness of thebatteries on the machine and the level of charging voltages on the network. In the actual operating conditions of the RB, there is a need to assess their technical condition, disassemble them for t oubleshooting, maintain their availability and extend their service life. RB degradation is reflected in the internal support of the battery cells. Determining the internal resistance of the RB is based on the Ohm dependencies of the complete circle and reduces to a system of two equations. RB life can be considered one of its most important performance characteristics. The relationship between battery life and itsestimated residual service life is nonlinear. Proper selection of chargers, skilled operation and timely monitoring of RB's residual life are the mostimportant requirements for their operation.

Предметом вивчення в статті є фізико-хімічні процеси, що протікають у акумуляторній батареї при різних умовах і термінах експлуатації. Метою дослідження є на основі аналізу умов експлуатації АБ розробити методику оцінки залишкового експлуатаційного ресурсу акумуляторних батарей дати рекомендації по подовженню термінів їх служби. Задачі: проаналізувати вплив умов експлуатації стартерних акумуляторних батарей на їх працездатність та терміни служби; зробити аналіз існуючих методів визначення залишкового експлуатаційного ресурсу акумуляторних батарей; дослідити залежності відхилення імпедансу від штатного значення для акумуляторних батарей у різні моменти їх штатного терміну експлуатації та розробити методику прогнозування залишкового експлуатаційного ресурсу АБ. Отримані такі результати. На основі знятих показань амперметра та вольтметра при вмиканні АБ у коло при різних значеннях навантаження та за даними, отриманими при проведенні КТЦ, було досліджено залежність відхилення імпедансу від базового значення при різних штатних термінах служби батарей. За методикою, що пропонується, шляхом отримання мінімальної кількості значень електричних параметрів акумуляторної батареї та зіставлення отриманих в різний час даних нескладно визначити, в яких батареях деградація тільки почалася, а в яких досягла рівня, коли їх необхідно замінити, не чекаючи фатального збою. Правильний підбір зарядних пристроїв, кваліфікована експлуатація та своєчасний контроль залишкового ресурсу АБ є найголовнішою вимогою їх експлуатації. У штатно працюючих батарей з часом з-за природного зносу внутрішній опір починає зростати. Істотне відхилення від норми в меншу сторону свідчить про явні несправності, таку батарею необхідно замінити незалежно від терміну її використання. Коли відхилення від базового рівня перевищує 25 %, батарею пора замінити. Проведені дослідження виявили нелінійні залежності між терміном експлуатації акумуляторної батареї та її прогнозованим залишковим експлуатаційним ресурсом. Висновки. Забезпечення належного рівня готовність техніки до використання у значній мірі залежить від стану АБ. Найбільший вплив на працездатність і термін служби акумуляторних батарей здійснюють температурні умови, ступінь розрідженості акумуляторних батарей на машин та рівень зарядних напруг в бортовій мережі. В реальних умовах експлуатації АБ виникає необхідність оцінки їх технічного стану, розбиранню для усунення несправностей, підтримки у встановленому ступеню готовності та подовжуванню терміну служби. Деградація АБ відбивається на внутрішньому опорі елементів батареї. Визначення внутрішнього опору АБ ґрунтується на залежностях закону Ома для повного кола та зводиться до розв’язання системи двох рівнянь. Термін служби АБ можна вважати однією з її найважливіших експлуатаційних характеристик. Залежності між терміном експлуатації акумуляторної батареї та її прогнозованим залишковим експлуатаційним ресурсом носять нелінійний характер. Правильний підбір зарядних пристроїв, кваліфікована експлуатація та своєчасній контроль залишкового ресурсу АБ є найголовнішою вимогою їх експлуатації.
Визначення залишкового експлуатаційного ресурсу стартерних акумуляторних батарей шляхом дослідження імпедансу при різних термінах служби
Keywords: internal current source resistance; внутрішній опір джерела струму